2012
DOI: 10.1021/je300466a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Propane. IV. Speed of Sound in the Liquid and Supercritical Regions

Abstract: Comprehensive and accurate measurements of the speed of sound in pure propane have been carried out in the liquid and supercritical regions by a double-path-length pulse-echo technique. The measured data cover the temperature range from (240 to 420) K with pressures up to 100 MPa. The measurement uncertainties amount to 3 mK for temperature, 0.01 % for pressures below 10 MPa, and 0.005 % for pressures between 10 MPa and 100 MPa, and 0.02 % for speed of sound. The high accuracy of the measurements is demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
1
22
2
Order By: Relevance
“…The RMS deviation of the calibration equation from the measurements was 0.010 %. Combining, in quadrature, the deviation of the EOS from the data of Meier and Kabelac [40] with the deviation of the path-length calibration equation from the present measurements yields an estimated combined standard uncertainty of 0.016 % in our speed of sound measurements. This represents a conservative estimate of the uncertainty since it is likely that a portion of the difference between the path-length calibration and the present data is due to systematic deviations between the EOS and the data of Meier and Kabelac.…”
Section: Calibration Of Path-length Difference and Measurement Uncertmentioning
confidence: 66%
See 1 more Smart Citation
“…The RMS deviation of the calibration equation from the measurements was 0.010 %. Combining, in quadrature, the deviation of the EOS from the data of Meier and Kabelac [40] with the deviation of the path-length calibration equation from the present measurements yields an estimated combined standard uncertainty of 0.016 % in our speed of sound measurements. This represents a conservative estimate of the uncertainty since it is likely that a portion of the difference between the path-length calibration and the present data is due to systematic deviations between the EOS and the data of Meier and Kabelac.…”
Section: Calibration Of Path-length Difference and Measurement Uncertmentioning
confidence: 66%
“…This represents a conservative estimate of the uncertainty since it is likely that a portion of the difference between the path-length calibration and the present data is due to systematic deviations between the EOS and the data of Meier and Kabelac. [40] When reporting the uncertainties in experimental data it is customary to combine the effects of the state-point uncertainty (i.e., the effects of the uncertainties in temperature, pressure, and composition) with those in the uncertainty of the primary measurand (i.e., the speed of sound):…”
Section: Calibration Of Path-length Difference and Measurement Uncertmentioning
confidence: 99%
“…Dzida and co-workers have studied u(T,P) for n-alkanes, alcohols and their mixtures, and have discussed their results from a physical chemistry point of view. The research groups of Lago et al, [91][92][93][94][95][96][97][98][99][100] Kabelac et al, [101][102][103][104] Guedes et al, [106][107][108][109] Trusler et al [110][111][112] and others 105,113,114 have reported measurements of u(T,P) on compounds such as: water, hydrocarbons, refrigerants, oils over a wide range of temperature and pressure. Research on the u(T,P) for biomassderived fuels and related compounds has recently been reported.…”
Section: Speed Of Sound In Liquid Organic Compoundsmentioning
confidence: 99%
“…In recent studies, we have measured comprehensive data sets of the speed of sound in liquid and supercritical ethane, propane, and normal butane by a double-path-length pulse-echo technique over a wide range of temperature and at high pressures of up to 100 MPa. With this work, we continue these studies for isobutane.…”
Section: Introductionmentioning
confidence: 99%